Small Business in Russia Through the Prism of a National Project - I. A. Kirichenko; V. V. Koshenskov (Мир новой экономики, 2021)
The article presents the results of the implementation of the National Project “Small and Medium Business and Support for Individual Entrepreneurial Initiatives” and federal projects included in it: “Improving the conditions for doing business”; “Expanding the access of small and medium-sized businesses to financial resources, including concessional financing”; “Acceleration of small and medium-sized businesses”; “Creation of a support system for farmers and the development of rural cooperation”; “Popularisation of Entrepreneurship”. We critically analysed the national project as a whole and assessed the newest situation of small and medium-sized businesses. Further, we carried out the analysis of the achievement of the leading indicators of the national project. Also, we considered the financing and the results of the achievement of indicators in the context of federal projects that are part of the national project for 2018-2020.We assessed the risks of non-fulfilment of the goals and objectives set in the projects. The article also examines the effectiveness and evaluates the effectiveness of state support measures for small and medium-sized businesses affected by the spread of coronavirus infection in 2020. Besides, we analysed the main changes in the regulatory legal framework within the framework of implementing the national project. The analysis of the updated structure and activities of the national project “Small and Medium Enterprises and Support for Individual Entrepreneurial Initiatives” has been carried out.